Outbreaks of cholera, capitalism and humanitarianism: Power grabs and the unmaking of corporeality in Haiti and the Dominican Republic - Agathangelou, Anna M. (The Greek Review of Social Research, 2013)
The outbreak of cholera in Dominican Republic and Haiti following the 2010 Haitian earthquake led to shoring up national security regimes and placing the Haitian black body and Haitian lands under intense scrutiny of geopolitical debates about humanitarianism and reconstruction. Reconstruction and biosecurity discourses, engaging with disease risks and minimizing contagion, deemphasized the various forms of slaughtering, death and profit making endeavors by foreign sovereign states and organizations desiring to secure an imperial position in the world through a politics of slavery and wiping clean Haitian landscapes. The struggles of Haitians highlight how the imaginary and practices of neoliberal governance depend on terror and rendering vast populations as living dead.